Supporting health literacy using an interactive app for symptom management during radiotherapy for prostate cancer. Issue 2 (February 2021) - Sundberg, Kay; Lindström, Veronica; Petersson, Lena-Marie; Langius-Eklöf, Ann
Highlights: Patient-reported outcomes were collected through an app during cancer treatment. Health literacy and self-care were assessed to see the supportive role of the app. Some patients reported low health literacy running a risk of poorer health outcomes. Advanced health literacy skills improved with the support of the app. Abstract: Objective: Patients' ability to self-monitor symptoms and engage in self-care activities is dependent upon their level of health literacy. Health literacy and self-care ability was compared in men with prostate cancer undergoing radiotherapy that used an app for symptom management with a control group. Methods: Included were an intervention group (n = 66), who used an app for symptom reporting and support for self-care, and a control group (n = 64). Outcomes were Functional Health Literacy, Communicative and Critical Health Literacy and Appraisal of Self-Care Agency (ASA-A). Results: The intervention group had improved regarding "ability to select information needed from a variety of information sources" (p = .020), "ability to determine the information credible" (p = .041), and "being able to plan and decide what to do to improve health" (p = .004). No inter-group difference was found for ASA-A. Conclusions: With the support of an app for reporting and managing symptoms, important advanced health literacy skills of selecting, determining, and judging information credible may improve. Practice implications: Patients undergoing treatment for prostate cancer may benefit from an individualized approach, such as an app, for communication with health care providers and as a source of health information to make decisions about their own health.